Bioequivalence assessment of two formulations of ibuprofen - Al-Talla ZA; Akrawi SH; Tolley LT; Sioud SH; Zaater MF; Emwas AHM (Dove Medical Press, 2011)
Zeyad A Al-Talla1, Sabah H Akrawi2, Luke T Tolley3, Salim H Sioud1, Mohammed F Zaater4, Abdul-Hamid M Emwas1 1Analytical and NMR Core Laboratories, King Abdullah University of Science and Technology, Thuwal, Kingdom of Saudia Arabia; 2College of Pharmacy, Al-Ain University, Al-Ain, United Arab Emirates; 3Department of Chemistry and Biochemistry, Southern Illinois University Carbondale, Carbondale, IL, USA; 4Department of Chemistry, Jordan University of Science and Technology, Jordan University of Science and Technology, Irbid, Jordan Background: This study assessed the relative bioavailability of two formulations of ibuprofen. The first formulation was Doloraz®, produced by Al-Razi Pharmaceutical Company, Amman, Jordan. The second forumulation was Brufen®, manufactured by Boots Company, Nottingham, UK. Methods and results: A prestudy validation of ibuprofen demonstrated long-term stability, freeze-thaw stability, precision, and accuracy. Twenty-four healthy volunteers were enrolled in this study. After overnight fasting, the two formulations (test and reference) of ibuprofen (100 mg ibuprofen/5 mL suspension) were administered as a single dose on two treatment days separated by a one-week washout period. After dosing, serial blood samples were drawn for a period of 14 hours. Serum harvested from the blood samples was analyzed for the presence of ibuprofen by high-pressure liquid chromatography with ultraviolet detection. Pharmacokinetic parameters were determined from serum concentrations for both formulations. The 90% confidence intervals of the ln-transformed test/reference treatment ratios for peak plasma concentration and area under the concentration-time curve (AUC) parameters were found to be within the predetermined acceptable interval of 80%–125% set by the US Food and Drug Administration. Conclusion: Analysis of variance for peak plasma concentrations and AUC parameters showed no significant difference between the two formulations and, therefore, Doloraz was considered bioequivalent to Brufen. Keywords: ibuprofen, bioequivalence study, pharmacokinetics